STRATEGI COPING STRES UNTUK ANAK BROKEN HOME PASCA PERCERAIAN KEDUA ORANG TUANYA DI DAERAH KAB. KARAWANG - Gita Febrianti; Amirudin Amirudin; Iqbal Amar Muzaki (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2022)
This study aims to determine stress coping strategies for children from a broken home after the divorce of their parents. This research is qualitative. This study tells about the background of the subject's life while the informants are 3 people. The results showed that the subject experienced changes in behavior, emotions, and physical it was caused by the stress he experienced. There are several factors that influence the subject to undergo stress coping, namely physical health, positive beliefs, problem solving skills, social skills, social support, as well as material. This research is qualitative. Methods of data collection using observation and interviews. The results of this study are that the subject can begin to open up to the environment and can be more mature in dealing with problems